Morphogenetic Alterations of Alternaria alternata Exposed to Dicarboximide Fungicide, Iprodione - Eunji Kim; Hye Min Lee; Young Ho Kim (The Plant Pathology Journal, 2017)
Fungicide-resistant Alternaria alternata impede the practical control of the Alternaria diseases in crop fields. This study aimed to investigate cytological fungicide resistance mechanisms of A. alternata against dicarboximide fungicide iprodione. A. alternata isolated from cactus brown spot was cultured on potato-dextrose agar (PDA) with or without iprodione, and the fungal cultures with different growth characteristics from no, initial and full growth were observed by light and electron microscopy. Mycelia began to grow from one day after incubation (DAI) and continued to be in full growth (control-growth, Con-G) on PDA without fungicide, while on PDA with iprodione, no fungal growth (iprodione-no growth, Ipr-N) occurred for the first 3 DAI, but once the initial growth (iprodione-initial growth, Ipr-I) began at 4–5 DAI, the colonies grew and expanded continuously to be in full growth (iprodione-growth, Ipr-G), suggesting Ipr-I may be a turning moment of the morphogenetic changes resisting fungicidal toxicity. Con-G formed multicellular conidia with cell walls and septa and intact dense cytoplasm. In Ipr-N, fungal sporulation was inhibited by forming mostly undeveloped unicellular conidia with degraded and necrotic cytoplasm. However, in Ipr-I, conspicuous cellular changes occurred during sporulation by forming multicellular conidia with double layered (thickened) cell walls and accumulation of proliferated lipid bodies in the conidial cytoplasm, which may inhibit the penetration of the fungicide into conidial cells, reducing fungicide-associated toxicity, and may be utilized as energy and nutritional sources, respectively, for the further fungal growth to form mature colonies as in Ipr-G that formed multicellular conidia with cell walls and intact cytoplasm with lipid bodies as in Con-G.